Uji Validitas Sesajen Berdasarkan Surah Al-Baqarah Ayat 170: Studi Kasus di Desa Sumberejo Kecamatan Pagar Merbau - Widya Puspita Sari; Achyar Zein; Muhammad Akbar Rosyidi Datmi (Yayasan Albahriah Jamiah Indonesia, 2026)
The practice of offerings persists in some Muslim communities as an expression of local traditions believed to have symbolic and protective functions. At the same time, Islamic teachings emphasize the purity of monotheism, thus creating normative tensions between culture and religious texts. The focus of this study is to test the validity of the practice of offerings through the recitation of Surah al-Baqarah verse 170, to assess its suitability from the perspective of the Qur’an. A qualitative case study-based approach was applied in Sumberejo Village, Pagar Merbau District through field observation techniques, in-depth interviews, and documentation, then analyzed using thematic interpretation to link the meaning of the verse to social reality. The results show that the practice of offerings is built on social constructions inherited from generation to generation, reinforced by cultural authority and collective beliefs about salvation. The analysis of the verse reveals criticism of the attitude of following traditions without rational basis and revelation, so that the practice of offerings is considered to have no legitimacy within the framework of monotheism. The validity test shows the inconsistency between local practices and the basic principles of Islamic teachings that reject all forms of symbolic intermediaries in requests for protection. The implications of this study enrich the development of contextual interpretations that are responsive to cultural realities and emphasize the dynamic relationship between religion and tradition in contemporary Muslim society.